A Secure Online Booking System with OTP for Sultans Spa Resort - ALGHAIL, AONI ALI MOHAMMED MOHAMMED; khaled, Shamsul (Applied Information Technology And Computer Science, 2025)
Sultans Spa Resort in Riyadh, Saudi Arabia, currently relies on phone calls and in-person visits for booking appointments, which limits scalability, efficiency, and security. This traditional approach exposes the system to risks such as unauthorized access and data breaches, compromising sensitive customer information and disrupting business operations. To address these challenges, this project proposes a secure online booking system with advanced features, including one-time password (OTP) authentication to enhance data protection and ensure secure user authentication. Guided by the Agile methodology, the project ensures flexibility, iterative progress, and continuous feedback to meet evolving customer needs and security requirements. The system will automate key spa operations such as appointment scheduling, customer account management, and real-time availability checks, leveraging technologies like HTML, CSS, PHP, JavaScript, and MySQL. This web-based platform aims to streamline booking processes, improve operational efficiency, and deliver a secure and user-friendly experience for customers. The system’s functionality and security will be thoroughly validated through alpha and beta testing to ensure reliability and effectiveness. By adopting this system, Sultans Spa Resort seeks to position itself as a leader in the hospitality industry, fostering long-term success, customer loyalty, and robust protection of sensitive customer information.